Scaled Conjugate Gradient Artificial Neural Network-Based Ripple Current Correlation MPPT Algorithms for PV System - Abdullah M. Noman; Hamed Khan; Hadeed Ahmed Sher; Sulaiman Z. Almutairi; Mohammed H. Alqahtani; Ali S. Aljumah (International Journal of Photoenergy, 2023)
This article proposes a hybrid scheme of maximum power point tracking (MPPT) based on artificial neural network (ANN) and ripple current correlation (RCC). ANN model is established using the data generated through RCC MPPT. Scaled conjugate gradient ANN is applied to gauge the performance improvement. The proposed scheme is validated through simulations. For this, the proposed system is applied to three different environmental scenarios which are standard testing condition of a PV module, under variable irradiance condition, and variable temperature condition. It is established that the proposed system is well capable of tracking the maximum power point under various test conditions.